Everyday Resilience: Equipping Faculty With Practical Exercises to Promote Resilience Among Medical Students - Galina Gheihman; Tara A. Singh; Cynthia A. Cooper; Bri Anne McKeon; David A. Hirsh; Arabella L. Simpkin (Association of American Medical Colleges, 2021)
Introduction Burnout is prevalent in health care. As professionals advocate to increase resilience training as a strategy to reduce burnout, few examples exist of practical resilience programs that equip faculty to help students build and sustain well-being over time. Method We developed two straightforward, skills-based resilience exercises. Breaking Down Easy taught individuals to identify personal strengths. My Resilience Practice helped individuals identify strategies to cope with daily stressors. We taught these exercises to international faculty in a train-the-trainer workshop format, at two medical education conferences. Faculty applied the exercises, performed pair-share reflections, and discussed opportunities to introduce the exercises in their own institutions. Postsession surveys evaluated the workshop quality and the exercises' ease of use and applicability. Results Thirty-five faculty and five students participated across two international conferences. Of participants, 83% (33 of 40) completed postsession surveys. On a 5-point Likert scale, participants rated the workshop on average 4.4 for usefulness, 4.6 for applicability, 4.4 for ease of instruction, 4.5 for clarity, and 4.8 for overall quality. Participants found the exercises to be straightforward to use and planned to use them at their institutions with students, residents, and faculty. Discussion Participants found our workshop to be relevant and effective and shared their intention to incorporate these materials into their teaching with medical students, residents, and faculty. Implementing effective programs to build resilience is critical to increasing well-being and reducing burnout. This, in turn, may enhance patient safety and improve health system outcomes.